2021
DOI: 10.3389/fcell.2021.633195
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase 3α Is Involved in Homologous Recombination Repair and Replication Stress Response in Trypanosoma cruzi

Abstract: DNA topoisomerases are enzymes that modulate DNA topology. Among them, topoisomerase 3α is engaged in genomic maintenance acting in DNA replication termination, sister chromatid separation, and dissolution of recombination intermediates. To evaluate the role of this enzyme in Trypanosoma cruzi, the etiologic agent of Chagas disease, a topoisomerase 3α knockout parasite (TcTopo3α KO) was generated, and the parasite growth, as well as its response to several DNA damage agents, were evaluated. There was no growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…These proteins can be divided into three groups: proteins able to bind/interact with DNA or RNA; proteins linked with ribosome biogenesis and maintenance; other proteins. The most interesting proteins from the first group (proteins able to interact with DNA or RNA) were the following: DNA topoisomerase 3α (involved in homologous recombination and torsion stretch relaxation [ 35 ]) and the plant-unique protein KAKU4 (responsible for nuclear morphology in plants [ 36 ]). In addition, our data also indicate the G4-interacting potential for the following: TF II D-subunit 15b (transcription initiation factor), RNA-binding family protein (RRM/RBD/RNP motifs) responsible for RNA splicing, the serine/arginine-rich splicing factor RSZ21 (mRNA processing [ 37 ]), the mediator of RNA pol II-transcription subunit 36a (mediator of RNA polymerase II), protein decapping 3α (translation repressor), and proteins belonging to the Argonaute family (AGO2 and AGO3, which contain the NIQI motif).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins can be divided into three groups: proteins able to bind/interact with DNA or RNA; proteins linked with ribosome biogenesis and maintenance; other proteins. The most interesting proteins from the first group (proteins able to interact with DNA or RNA) were the following: DNA topoisomerase 3α (involved in homologous recombination and torsion stretch relaxation [ 35 ]) and the plant-unique protein KAKU4 (responsible for nuclear morphology in plants [ 36 ]). In addition, our data also indicate the G4-interacting potential for the following: TF II D-subunit 15b (transcription initiation factor), RNA-binding family protein (RRM/RBD/RNP motifs) responsible for RNA splicing, the serine/arginine-rich splicing factor RSZ21 (mRNA processing [ 37 ]), the mediator of RNA pol II-transcription subunit 36a (mediator of RNA polymerase II), protein decapping 3α (translation repressor), and proteins belonging to the Argonaute family (AGO2 and AGO3, which contain the NIQI motif).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst pyrazoloquinazolines do not have reported activity against trypanosomes, compounds from this class have demonstrated inhibition of human topoisomerase I [ 60 ]. Topoisomerase has been identified as a target in trypanosomes and has recently been implicated in response to replication stress in T. cruzi [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that amastigote and epimastigote dormancy is strain-dependent in T. cruzi and it is directly correlated with mRNA TcRAD51 levels, a recombination pivot, responsible for strand invasion and search for homology between broken strand and the template (Baumann and West, 1998;Gomes Passos Silva et al, 2018;Resende et al, 2020). Costa-Silva et al (2021) demonstrated that DNA topoisomerase 3a (TcTopo3a) is important for homologous recombination repair and replication stress in T. cruzi. TcTopo3a gene knockout inhibited the amastigote proliferation and a high number of dormant cells was identified.…”
Section: Discussionmentioning
confidence: 99%